Nomadic computing?an opportunity. - Kleinrock, Leonard
We are in the midst of some truly revolutionary changes in the field of computer-communications, and these offer opportunities and challenges to the research community. One of these changes has to do with nomadic computing and communications. Nomadicity refers to the system support needed to provide a rich set of capabilities and services to the nomad as he moves from place to place in a transparent and convenient form. This new paradigm is already manifesting itself as users travel to many different locations with laptops, PDA's, cellular telephones, pagers, etc. In this paper we discuss some of the open issues that must be addressed as we bring about the system support necessary for nomadicity. In addition, we present some of the considerations with which one must be concerned in the area of wireless communications, which forms one (and only one) component of nomadicity.
Keywords: Computer systems organization; Computer communication networks; Data communications; Special purpose and application based systems; Signal processing systems; Design; Performance